Design Of "JOGJAVA" Mobile Application with Augmented Reality Technology Features as A Media Tourism Experience in Yogyakarta - Saffana, AlifaNur; Wiranatakusuma, Dimas Bagus (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
Tourism is an important sector of economic growth. The number of tourist attractions in Jogjakarta increased foreign tourist visits to the Special Region of Yogyakarta by 3.46% in March 2023. This increase is inseparable from the development of information technology and the sophistication of communication. The use of a technology is necessary to realize the equitable introduction of Yogyakarta Special Area attractions and be able to describe tourist attractions in real terms. The solution is by utilizing technology that can package the potential of tourist attractions attractively, attractively and today. One of the technologies that we can use is Augmented Reality, which can be used through the Hand Phone (HP) with the Screen application facility. Like the JogJava application created in this study. JogJava application is desin to provide tourist information with features that use AR technology. This research was made using research and development methods.